Características dos sistemas de controle gerencial de universidades brasileiras: estudo de casos de universidades localizadas no estado do Rio de Janeiro - Cardozo, Hugo Leonardo Guilhernandes (2014)
The aim of this thesis was to describe and understand how it is implemented and monitored management controls and how they are developed within the environment of private and public universities. Considering the nature of the theme and objectives of this study, we chose an approach to qualitative research. Data analysis revealed which factors affect the process controls in these universities, their characteristics, the actors involved in the process and finally the relationship between planning and performance. Found large differences in the results of controls were identified and studied in universities in structure between institutions of higher education both public and private, where different management concepts was observed within the same standard of service offered. These differences appear to be critical to the growth and qualification in the field where they operate.